A multifactor analysis of the rail transport car that passes over a joint unevenness with respect to the phases ot its motion - Shpachuk, Vladimir; Chuprynin, Aleksandr; Suprun, Tatiana; Garbuz, Alla (Eastern-European Journal of Enterprise Technologies, 2018)
We have studied the influence of loading a four-axle railroad car, geometrical and mechanical characteristics of the rail, joint bars, sleepers, and a ballast layer on the parameters of static interaction between a railroad car and a rail track. The results obtained are universal and apply to railroad cars of any purpose: tram cars or passenger or freight cars for railroad transportation. The discrete-continuum model of the transport complex "railroad car − rail track" corresponds to the phase of car motion. The estimation schemes of static interaction relate to all four phases of the railroad car motion, as well as geometrical and structural parameters of the track dispatching and receiving rails and a four-axle railroad car. The structure of the research method and numerical algorithm implies determining the deflections of the track dispatching and receiving rails at the end, as well as the height of the joint that emerges in this case, depending on the car load. Research into the influence of operating and structural parameters of a railroad car and the upper structure of a track on the static interaction between a railroad car and a rail track in the zone of a butt joint was carried out based on a comprehensive approach and general correlations in mechanics. We have calculated, in the transport systemic discrete-continuum mechanical complex "railroad car − rail track", using the methods of modeling and numerical analysis, the height of a joint unevenness depending on the phase of motion and load of the car. We established a parabolic character of the impact of a car load on the static interaction when passing over a joint unevenness, which corresponds to a monotonous growth in the height of a joint when increasing the load of a railroad car at all phases of its motion. The obtained theoretical results allow practical implementation of the improvement of structural and operating parameters in the operation of a railroad car and the upper structure of a track through rational selection and optimization.